Retrieving knowledge and information by using a systematic search interface – an industrial case study - Luft, Thomas; Wartzack, Sandro (DS 71: Proceedings of NordDesign 2012, the 9th NordDesign conference, 2012)
Knowledge and information are nowadays the most important factors for the development of modern and innovative products. Therefore the efficient management and contextual supply of knowledge is nowadays becoming increasingly essential because more knowledge and information needs to be considered by engineers. However, there are a variety of problems in handling and retrieving knowledge and information in particular in the engineering design process. Existing IT systems do not meet the requirements of the users or do it only in an insufficient way. In this paper which is based on an industrial case study the identification and in particular the classification of “Knowledge and Information-Objects” of the considered company is described. These two steps are one of the most important preconditions for a holistic and computer-based knowledge management system from a management and a supply oriented view. In order to customise a systematic search interface that meets the requirements of the employees, an appropriate number of workshops with experts from different departments have to be organised. The focus of this paper is on a (combined) content- and source-based systematic search interface for knowledge and information retrieval.
Keywords: knowledge management; product development; requirement analysis; information storage; information retrieval; industrial case study